Determining the Perceived Information Literacy on HIV/AIDS of Senior High School Students - Calista, Eva; Bhattrai, Juvy Lou; Licong, Lea; Agum, Arjem Noryn; Balila, Jolly; Aclan, Eunice (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
HIV/AIDS is a social problem in Indonesia. Teenagers account for most HIV/AIDS cases in Bogor, West Java; thus, the issue of whether they are HIV/AIDS literate needs to be addressed. This study aims to find the level of information literacy on the perception of HIV/AIDS among senior high school students in terms of recognition of information needs on HIV/AIDS, location, and evaluation of information on HIV AIDS, storage and retrieving information, and the effective use of information. It also determines if there was a significant difference in information literacy on the perception of HIV/AIDS when the respondents were clarified into age and sex. This study employed a quantitative research approach with a descriptive analysis design that was carried out among senior high school students in Caringin, Bogor, Indonesia, in April 2021 as no study within the exact context has chosen the school as the respondents. There were a total of 131 respondents, with 33 males and 98 females. The findings indicated that except for the level of storage and retrieving information, which was moderate, the respondents’ level of information literacy from the dimension such as recognition of information needs on HIV/AIDS, the level on location and evaluation of information on HIV/AIDS, and the level of effective use of information was high. The study also found no significant difference in information literacy between males and females and among three different age groups. Keywords : Perceived Information Literacy, HIV/AIDS, high school, Indonesia